Variabel Fundamental Perusahaan Dalam Memprediksi Hedging Decision (Studi Perusahaan Automatif dan Komponen Serta Pertambangan Batubara Periode Tahun 2014-2017) - Sofyan Hadinata; Diah Anggari Hardianti (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
One of the major risks facing multinational companies in international trade is the risk of fluctuations in foreign exchange rates. The company makes an effort to reduce the impact of these risks through risk management using a hedging decision. This study aims to test empirically the effect of the company's fundamental variables in predicting hedgings decision. Fundamental variables in this study use financial ratios, namely profitability, leverage, liquidity and growth opportunities. The data in the study used panel data from 2014 to 2017. This study used data analysis techniques using logistic regression tests. Logistic regression test is used because the dependent variable uses dummy data, namely companies that do hedging are given a score of 1 and those who do not do hedging are given a score of 0. The results of the study show that the variable profitability, leverage, and growth opportunities have a positive effect on the hedging decision. The variable liquidity has a negative effect on the hedging decision.